PENGARUH PERBEDAAN JENIS PAKAN ALAMI DAPHNIA, JENTIK NYAMUK DAN CACING SUTERA TERHADAP PERTUMBUHAN IKAN CUPANG HIAS ( Betta splendens ) The Effect of Different Types Of Natural Food Daphnia, Mosquito Larvae and Silk Worms to Growth of Ornamental Fish Bett - Muhammad Agus; Tri Yusufi Mardiana (Fakultas Perikanan Universitas Pekalongan, 2015)
This study aims to determine the effect of different natural feeding of Betta fish growth and to know what types of natural food that provides growth Betta fish is best. Research was conducted that the Laboratory of Aquaculture Faculty of Fisheries University of Pekalongan on the date of 12 June to 12 July 2010. This study used a complete randomized desaign with 3 treatments and each treatment is repeated 3 times. The treatment applied are different types of natural food is Daphnia sp, mosquito larva an silk Worm. Results of analysis of variance showed that differences in types of natural food which is given a very real effect on the growth of Betta fish. Tukey’s test further showed that the treatment using silk Worms were significantly different to the treatment using mosquito larva and treatment using Daphnia sp. The range of water quality during the study are still eligible for the maintenance of Betta fish. namely the water temperature tranges between 26 – 30oC, the pH of water range from 7-8 and DO ranged between 3.7 to 5.4 ppmKey word : Ornamental cupang, Daphnia sp, mosquito larvae, silk worm